Witness to a Giant's Toils - Brandler, J.F (Nigeria, 1993)
This are the memoirs of J.L. Brandler who built up one of the largest timber producing and exporting companies in Nigeria. They also tell the story of Nigeria's development from a colonial dependency to an independent state...
Keywords: Biography & Autobiography; J.L. Brandler; Nigeria Social Life & Custom; Non-Fiction